Testing the theory of Differential Susceptibility to nightmares: The interaction of Sensory Processing Sensitivity with the relationship of low mental wellbeing to nightmare frequency and nightmare distress - Michelle Carr (Journal of Sleep Research, 2021)
Propensity to have nightmares has been theorisd in terms of diathesis–stress models, with this propensity being seen as negative or even pathological. In contrast, a recent model proposes that nightmare propensity is due to Differential Susceptibility to stimuli, where high susceptibility can be beneficial in positive environments but detrimental in negative environments. This susceptibility to stimuli is assessed as the biobehavioural trait Sensory Processing Sensitivity, which refers to a greater responsivity to internal and external stimuli, and an increased depth of cognitive and emotional processing. To test the Differential Susceptibility Framework for nightmares, 137 participants (females = 104, males = 33; mean age = 33.66 years), recruitedfrom a student population and social media sites, were divided into high(n = 39), medium (n = 59) and low (n = 39) Sensory Processing Sensitivity categories based on their score on the Highly Sensitive Person Scale. Low mental wellbeing and the presence of minor psychiatric problems, measured by the General Health Questionnaire, was found to be significantly correlated with nightmare frequency for the high and medium SPS groups (rs = .29 and .28, respectively), but not for the low Sensory Processing Sensitivity group (r = .19). General Health Questionnaire score was also significantly correlated with trait nightmare distress, for the high Sensory Processing Sensitivity group only (r = .32). These findings in favour of the Differential Susceptibility Framework have aetiology and treatment implications for nightmares that differ from diathesis–stress models.